Evaluation of Tongue Volume and Airway Volume in Skeletal Class I and Class II Patients using Cone Beam Computed Tomography- A Cross Sectional Study - Jim Thomas Abraham; Roshan M Sagarkar; Sharanya Sabrish; Prashantha Govinakovi Shivamurthy; Silju Mathew; Nagaraju Rakesh (University Library System, University of Pittsburgh, 2023)
BACKGROUND: The volumetric relationship between the tongue and the oral cavity is an important factor in tooth alignment and occlusion. The aim of this study was to evaluate the difference in tongue and airway volume in skeletal Class I and Class II malocclusion. MATERIALS AND METHODS: The CBCT data which comprised of 30 skeletal Class I and 30 skeletal Class II was stored in DICOM format. Tongue volume and airway volume was analyzed with the help of 3D dolphin software. Values obtained were subjected to statistical analysis with help of SPSS. RESULTS: Skeletal Class I pattern had more tongue volume with a mean of 45.32 mm3 than skeletal Class II pattern with mean value of 40.27mm3 with P value of <0.001. Skeletal Class I pattern has more airway volume with a mean of 15058.6 mm3 than patients with Skeletal Class II pattern with mean value of 12458.8mm3 with a P value of 0.003. A P value of 0.001 indicated that there is a strong correlation between the tongue volume and airway volume in both skeletal Class I and skeletal Class II subjects. CONCLUSION: The volume of tongue and airway was greater in skeletal Class I malocclusion compared to skeletal Class II malocclusion. There exists a positive correlation between the tongue volume and airway volume in both the skeletal patterns.